RECONSTRUCTION OF THE ACCOUNTABILITY MODEL FOR CORPORATE SOCIAL RESPONSIBILITY (CSR) FUND MANAGEMENT - Rifdan, Hasnawi Haris, Haedar Akib, Siti Hasanah Nasution, Andi Aco Agus (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims to explain the reconstruction of the institutional role model in managing the Corporate Social Responsibility (CSR) program, a case study in Makassar City, Indonesia.Duties, Functions and Roles of the Corporate Social and Environmental Responsibility (COSER) Board are regulated through Makassar Mayor Regulation Number 28 of 2017. This type of qualitative research, in which data is obtained through interviews, observation and document review, uses interactive model analysis techniques through data condensation stages, data presentation, conclusion or verification. The results showed that the COSER Board that was formed had not been optimal in carrying out its main duties, functions and authorities, because currently there had been no sanctions against companies deemed to have violated regulations, even though there were some companies that have not distributed their CSR funds. There has not been good coordination by the COSER Board with several companies in the formulation and distribution of CSR programs, and there are still some companies that do not know the existence of the COSER Board. Therefore, a scheme for regulating main tasks, functions and institutional roles has been reconstructed in the form of a prototype model for effective and sustainable CSR Fund management in Makassar City.